Plan B converting change into career opportunity - Chapman, Elwood N. (Crisp Pub. Menlo ParkUS, 1993)
Explains the concept of, and necessity for Plan B. Addresses myths and misconceptions associasted with it. Presents a seven-step strategy for developing a Plan B. Step #7 explains how to market the plan. Provides a model for preparing a personal Plan B.